Electrocoagulation (EC) for Reduction of Chemical Oxygen Demand (COD) of Surface Water - Rahman, SH; Islam, SMN; Kaiser, N; Rahman, Md M (Bangladesh Journal of Scientific and Industrial Research, 2012)
Karnopara Canal water containing high COD values (1050 mg O2/L) was treated by electrocoagulation (EC) method covering a wide range of operating conditions such as, water pH, internal electrode distances, final pH, supplying 30V electricity for constant time period (30 minutes) through same electrode material (Al electrode). The effects of different operating parameters on the efficiency of the process were examined. Targeting to reduce the COD value within the recommended limit (200 mg O2/L), this research work was emphasized on EC treatment at the simplest and cheapest way. The batch experiment results showed that the high COD contained canal water can be effectively treated using electrocoagulation. The overall COD removal efficiencies have been obtained at 87.3%, under optimum operating conditions. Taking all the factors into account, it was found that polluted Karnopara canal water can be treated using EC consisting of Al electrodes without pre-adjustment of pH at laboratory. Therefore, EC technique to reduce high COD from canal surface water is found effective, cheaper and environmental friendly. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10728 Bangladesh J. Sci. Ind. Res. 47(1), 77-82, 2012